Reaction of rubber tree rootstock to Meloidogyne exigua and Pratylenchus brachyurus - Paes-Takahashi, Vanessa Dos Santos [UNESP]; Soares, Pedro Luiz Martins [UNESP]; Guiducci, Erika Perches [UNESP]; De Brito, Paulo Fernando; Carneiro, Franciele Alves [UNESP]; Ferreira, Rivanildo [UNESP] (My University, 2015)
The rubber tree, Hevea brasiliensis, is an important crop for São Paulo State, which produces more than 50% of the total Brazilian natural rubber. Nematode studies, especially with Meloidogyne exigua and Pratylenchus brachyurus, are limited. The rubber tree rootstocks 'GT1', 'PB-235', 'PB-217', 'RRIM-501', 'PR-255', 'IAN-873', 'RRIM-600', and 'TJ-1' were evaluated for these nematodes. Six-month-old seedlings were inoculated with 3,000 eggs + juveniles of M. exigua or 1,000 active forms + eggs of P. brachyurus, separately. In order to evaluate nematode tolerance, the plant height and diameter were measured, and total population, nematodes g-1, and the reproduction factor (RF) were evaluated for nematode resistance. Meloidogyne exigua caused more pronounced damage to the rubber tree rootstocks. All rootstocks were intolerant and susceptible to both M. exigua and P. brachyurus.
Keywords: Hevea brasiliensis; Lesion nematodes; Root-knot nematodes